Cyberbullying And Adolescent Mental Health In Timor-Leste: A Systematic Literature Review In The Context Of Lower-Middle-Income Southeast Asian Settings - Denadia Exposto Sarmento (EDUJAVARE: International Journal of Educational Research, 2026)
Cyberbullying is a well-established risk factor for adolescent mental health, yet the evidence base underpinning this conclusion is drawn overwhelmingly from high-income settings. Timor-Leste, the Asian country with the youngest population structure and one undergoing rapid digital expansion, is represented in no prevalence or outcome study of cyberbullying whatsoever. This review synthesises evidence on the association between cyberbullying victimisation and adolescent mental health in Timor-Leste and comparable lower-middle-income Southeast Asian settings, and characterises the structure of the resulting evidence gap. A systematic literature review with narrative synthesis was conducted across nine international databases, three regional databases, and six grey-literature repositories, covering publications from January 2005 to June 2026 without language restriction. No study reporting cyberbullying prevalence or cyberbullying-related mental health outcomes among Timorese adolescents was identified. Timor-Leste is represented solely by five secondary analyses of the 2015 Global School-based Student Health Survey, which recorded an offline bullying prevalence of 28.0% and an independent association between bullying victimisation and attempted suicide (AOR = 2.69, 95% CI [1.02, 7.12]). This absence of evidence is traceable to a specific and correctable instrumentation decision, namely the omission of cyberbullying items from the national survey instrument, rather than to an absence of risk. Timor-Leste satisfies every structural precondition for cyberbullying to constitute a public health problem, while its mental health workforce stands at approximately three professionals per 100,000 population. The priority action indicated is the inclusion of validated cyberbullying items in the next national school health survey cycle, preceded by the development of a Tetun-language measurement instrument.